Emotional reactions and stigmatization after a parricide in South Tyrol, Italy, among mental health professionals and the general population, including persons with mental disorders, relatives, and persons with no direct or indirect contact - Stockner, Mara; Wenter, Anna; Obexer, Artur; Gualtieri, Isabella; Merler, Francesca; Bennato, Davide; Conca, Andreas (Frontiers in Public Health, 2024)
This study was conducted on the occasion of the parricide in Bolzano (South Tyrol, Italy) in January 2021. The psychological impact of parricide on the general population and on mental health professionals has scarcely been investigated to the present day. Studies on stigmatisation show differences between various groups. The aim was to analyse the emotional reactions to the parricide and the stigmatisation of persons with mental disorders in the South Tyrolian population. In September 2022, 121 mental health professionals of the Department of Psychiatry in Bolzano were surveyed using an online questionnaire. In addition, from January to March 2023, the general population of South Tyrol was invited to take part in the survey through an online-link and was divided into three groups: 267 persons with mental health problems, 855 relatives and 1,019 persons with no direct or indirect contact to people with mental problems. The validated Reported and Intended Behaviour Scale (RIBS) was used together with questions on the emotional reactions to the parricide and the perceived dangerousness of psychiatric patients. Descriptive statistics, one-way Anovas as well as regressions were carried out. All groups experienced sadness the most. Relatives experienced more sadness and anger than the other groups. Over eighty percent of the professionals stated that psychiatric patients were not at greater risk of committing parricide. The population with no contact rated the risk higher than those affected and had the lowest level of openness (RIBS). There were no differences between genders, but there were age differences, with younger people being more stigmatising. The results suggest that personal contact, appropriate information, and education are associated with less stigmatisation.